Advokasi Kebijakan Rencana Pengelolaan Hutan Jangka Panjang tahun 2020-2029 Unit III Bungo - Rahmadita Anggraini; Muhammad Ichsan Kabullah; Nila Wahyuni (Journal of Administration, Governance, and Political Issues, 2026)
The purpose of this study is to describe the success of advocacy organizations in promoting changes to the 2020-2029 forest management plan for Unit III Bungo. The blocks that were originally planned for utilization turned out to be virgin forests, wildlife corridors, and buffer zones for the Kerinci Seblat National Park. The purpose of this study is to determine the reasons behind the success of the policy advocacy carried out by KKI Warsi and Yayasan PKHS in converting some of the utilization blocks into protected areas. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results showed that advocacy organizations utilized all forms of input, which were then used to carry out five activities, influencing and mobilizing the public, influencing decision makers, information campaigns, defensive activities, and policy monitoring. These various activities then resulted in a more democratic environment, changes in the views of policy makers, and the adoption and implementation of policies. However, advocacy only touched on the impact of substantive changes and not on changes in the mechanism of block distribution and public-centered policies.